Integrated project team performance in early design stages – performance indicators influencing effectiveness in bridge design. (4th July 2019) - Ekström, Daniel; Rempling, Rasmus; Plos, Mario
ABSTRACT: To create multi-functional and integrated project teams, and to adopt a team perspective in the early design stages, it is recognised in the literature that a more effective process is required; one that reduces the probability of costly changes and difficulties during construction. This paper presents an evaluation of project team collaboration during early design and development of construction documents for bridges in Sweden. The purpose was to study key variables influencing the performance of integrated project teams by using importance performance analysis (IPA). A self-evaluation questionnaire addressed clients, contractors, and structural engineering consultants in the Swedish bridge construction industry. The questionnaire addressed three essential cornerstones of value-creation during the engineering design process; culture, structure and competence. These were addressed at three organisational hierarchy levels, the organisation, project, and the individual level. Our results show that increased support and resources are required at the project level for better project team performance. Results further identify that project culture needs to be developed including both collaboration and social relationships as well as project competence, especially the ability to solve mutual issues. This research offers a 'generalised' and prioritised view of the challenges in the Swedish bridge construction industry in terms of creating integrated project teams.